A pH-responsive cascade nanoplatform with circulating oxygen supply for collaborative breast cancer treatment. Issue 86 (12th October 2022) - Gao, Xiaonan; Jia, Zhikai; Cheng, Yaoying; Ouyang, Mingyi; Feng, Lin; Wang, Yuzhuo; Tang, Bo; Xu, Kehua
Abstract : A pH-responsive cascade nanoplatform based on ZIF-8 disintegrates in the weakly acidic tumor microenvironment to release MnO2, CaO2 and Ce6. Abstract : A pH-responsive cascade nanoplatform based on ZIF-8 disintegrates in the weakly acidic tumor microenvironment to release MnO2, CaO2 and Ce6. The drugs can cyclically generate O2 for sonodynamic therapy, consume glutathione to tune the redox hemostasis, and produce cytotoxic ˙OH to kill tumor cells via chemical dynamics therapy.